Effects of steroid hormones on lipid metabolism in sexual dimorphism: A Mendelian randomization study - Liang, Junzhi; Zhang, Bowen; Hu, Yannan; Na, Zhijing; Li, Da (Frontiers in Endocrinology, 2023)
Background: Although the role of steroid hormones in lipid levels has been partly discussed in the context of separate sexes, the causal relationship between steroid hormones and lipid metabolism according to sex has not been elucidated because of the limitations of observational studies. We assessed the relationship between steroid hormones and lipid metabolism in separate sexes using a two-sample Mendelian randomization (MR) study. Methods: Instrumental variables for dehydroepiandrosterone sulfate (DHEAS), progesterone, estradiol, and androstenedione were selected. MR analysis was performed using inverse-variance weighted, MR-Egger, weighted median, and MR pleiotropy residual sum and outlier tests. Cochran’s Q test, the MR-Egger intercept test, and leave-one-out analysis were used for sensitivity analyses. Results: The results showed that the three steroid hormones affected lipid metabolism and exhibited sex differences. In males, DHEAS was negatively correlated with total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and apolipoprotein B (P = 0.007; P = 0.006; P = 0.041, respectively), and progesterone was negatively correlated with TC and LDL-C (P = 0.019; P = 0.038, respectively). In females, DHEAS was negatively correlated with TC (P = 0.026) and androstenedione was negatively correlated with triglycerides and apolipoprotein A (P = 0.022; P = 0.009, respectively). No statistically significant association was observed between the estradiol levels and lipid metabolism in male or female participants. Conclusions: Our findings identified sex-specific causal networks between steroid hormones and lipid metabolism. Steroid hormones, including DHEAS, progesterone, and androstenedione, exhibited beneficial effects on lipid metabolism in both sexes; however, the specific lipid profiles affected by steroid hormones differed between the sexes.